Estudo de transformadores de estado sólido para conexão de sistemas de geração distribuída à rede de distribuição de energia elétrica - Tiago Luiz Dias (2013)
This master thesis presents the study and simulation of a solid state transformer (SST) used for the purpose of promoting the parallelism of distributed energy sources with the power grid. Among the distributed generation technologies currently available it was decided to adopt photovoltaics, aiming the future development of a prototype for laboratory studies. A literature review is performed highlighting the main features and technical advantages that the SST presents, especially with regard to the energy quality at its output compared to traditional power transformers. By being an active component based on power electronics,compensation functionalities of grid disturbances can be added to the SST, making it a device technically superior to usual transformers. The technology for silicon carbide switches is also introduced for comparison with traditional semiconductor devices based on silicon. Such a technique has been presented as a viable alternative for applications of static power converters in high voltages. A study of the major theoretical aspects of control strategies used to achieve the parallelism of the SST with the grid is presented. The control structures responsible for regulating the dc bus voltage and controlling the injection of balanced currents into the grid are simulated and analyzed. Due to the presence of imbalances in the grid voltages and the predominance of 5th and 7th order harmonics in three phase system, control structures capable of performing the selective compensation of harmonics of positive and negative sequence present in the injected currents are studied and simulated. Thereby, the injection of a low harmonic content in the grid is achieved, in accordance with existing standards for distributed resource technologies. For this purpose, the transformation of the electrical quantities from the original phasorial system (abc) to multiple synchronous reference frames is studied and applied.